ANALYSIS OF THE QUALITY OF HEALTH SERVICES ON PATIENT SATISFACTION AT THE PUBLIC HEALTH CENTER : A LITERATURE REVIEW - Windarti, Aprilia; Toni Herlambang; Abadi Sanosra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine patient satisfaction with the quality of health services at the health center. Method: This article uses the literature review method following the PRISMA guidelines. Data was obtained from the Google Scholar electronic database. The keyword used was